Systematic approach of measuring program outcomes of management postgraduate program - Bohra, Narendra Singh; Johri, Amar; Wasiq, Mohammad (Frontiers in Education, 2024)
This study aims to develop a simplified approach for measuring the outcomes of academic programs. To achieve this, postgraduate management programs offered by various Indian institutions have been selected. Program outcomes (POs) and course outcomes (COs) are key measurement constructs. The course assessment strategy is tailored to the nature of each course, which is categorized into four distinct groups. Course outcomes (COs) of continual evaluation courses are measured through developed rubrics. This study concludes that a systematic assessment process and well-designed measurement tools are important for measuring program outcomes (POs) of academic programs like management postgraduate programs. We recommend our model of measuring learning outcomes for all institutions, where the management postgraduate programs offered courses are evaluated on three components: faculty assessment, mid-semester assessment, and end-semester assessment. This process ensures a comprehensive and accurate measurement of program outcomes.